The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.17116/oftalma201913502162
|View full text |Cite
|
Sign up to set email alerts
|

Complex assessment of retinal ischemic damage in patients with retinal vein occlusion

Abstract: Цель-оценить эффективность лечения и возможность восстановления зрительных функций у больных с окклюзией вен сетчатки (ОВС) в зависимости от степени исходной макулярной ишемии. Материал и методы. Обследовано 84 пациента с перенесенной ОВС. Основными критериями включения в исследование были наличие макулярного отека на фоне ОВС, не превышающей по длительности 3 мес, и отсутствие какого-либо предшествующего лечения. Всем пациентам выполнялись интравитреальные инъекции ингибитора ангиогенеза с последующим лазерны… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many studies have shown that when the internal retinal vein is occluded, the increased secretion of VEGF in the retina induces neovascularization, thereby resulting in either macular degeneration or vitreous opacity [ 107 ]. In the early stage of retinal ischemic disease, the thickness of the retina is normal, but the thickness of the optic nerve fiber layer is increased.…”
Section: Application Of Proteomics In Optic Nerve Injury Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that when the internal retinal vein is occluded, the increased secretion of VEGF in the retina induces neovascularization, thereby resulting in either macular degeneration or vitreous opacity [ 107 ]. In the early stage of retinal ischemic disease, the thickness of the retina is normal, but the thickness of the optic nerve fiber layer is increased.…”
Section: Application Of Proteomics In Optic Nerve Injury Diseasesmentioning
confidence: 99%
“…In the middle stage of ischemia, the optic nerve begins to atrophy, and the peripheral optic nerve fibers show clear swelling, but their thickness is still less than in the early stage. In the later stage, atrophy, thinning, and visual field changes occur [ 107 ] to signify that the optic nerve has been severely damaged and many RGCs in the retina have died. Retinal ischemic diseases may be related to hereditary diseases.…”
Section: Application Of Proteomics In Optic Nerve Injury Diseasesmentioning
confidence: 99%